On the indeterministic nature of star formation on the cloud scale - Geen, Samuel Thomas; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Molecular clouds are turbulent structures whose star formation efficiency (SFE) is strongly affected by internal stellar feedback processes. In this
Gesehen am 10.09.2019